Serum afamin levels in predicting gestational diabetes mellitus and preeclampsia: A systematic review and meta-analysis - Yuan, Ying; He, Wenyin; Fan, Xuejiao; Liang, Junyu; Cao, Zhen; Li, Lei (Frontiers in Endocrinology, 2023)
Objectives The association between biomarkers and the risk of gestational diabetes mellitus (GDM) or preeclampsia (PE) has been extensively studied. However, there is still a lack of convenient, specific, and sensitive indicators for early identification of GMD and PE. Therefore, we conducted a meta-analysis of published articles to investigate the value of afamin circulating levels in the early diagnosis of GDM and PE. Methods We searched the PubMed, Embase, Cochrane Library, and Web of Science databases for English studies published before November 16, 2022, that examined the association between afamin and GDM or PE. In addition, we searched Clinicaltrials.gov for the relevant completed and ongoing clinical trials. Pooled standard mean differences (SMDs) and weighted mean differences (WMDs) with 95% confidence intervals (CIs) were used to compare the levels of afamin in different groups. Results Eleven studies were included in our analysis (N = 3047 participants: 1195 GDM, 1407 non-GDM, 195 PE, and 250 non-PE). Subgroup analysis based on different blood collection periods found that the plasma afamin levels in pregnant women with GDM in the first trimester were significantly higher than those in healthy pregnant women (SMD = 0.481, 95% CI: 0.280-0.682), but the analysis showed the opposite results in the second and late stages (SMD = 0.292, 95% CI: -0.092-0.676). The plasma afamin levels of pregnant women with PE in the first trimester (SMD = 0.808, 95% CI: 0.558-1.059) and second/third trimesters (SMD = 0.904, 95% CI: 0.570-1.239) were significantly higher than those in healthy pregnant women. Conclusion The plasma afamin levels in pregnant women with GDM in the first trimester were significantly higher than those in healthy pregnant women, but the analysis showed the opposite results in the second and third trimesters. The plasma afamin levels in pregnant women with PE in the first, second, and third trimesters were significantly higher than those in healthy pregnant women. Additional large-scale prospective studies are desired to verify these findings, and it is recommended that afamin should be included as a routine diagnostic test for women with GDM and PE.